Primary Sources on Monsters : Demonstrare, Volume Two - Hensel, Marcus; Mittman, Asa Simon, 1976- (Arc reference., 2018)
University courses on monsters are becoming widespread as many disciplines use monsters to think about what it means to be human. To date no source collection on the literature of the monstrous exists, and this volume offers the key primary readings on monsters from ancient times to the present day. Each work is preceded by a critical introduction, reading questions, notes and further reading.